Penguatan Peran Orang Tua dalam Pengawasan Penggunaan Gadget di TK Dharmawanita 03 Pomahan: A Study on Dharmawanita 03 Pomahan Kindergarten - Sabila Tria Umaroh; Atika Mulia Maghfiroh; Elfa Naharotul Hikmah; Hestu Wilujeng (LSM Catimore dan Sahabat, 2024)
Gadgets provide extensive access to a variety of information and entertainment, but uncontrolled use can have a negative impact on children's development. Therefore, parents have an important role in accompanying early childhood when using gadgets. The Community Service Lecture through the Parenting Seminar was held at Kindergarten DHARMAWANITA 03 Pomahan. The holding of this seminar aims to make parents wise in regulating the use of gadgets in children. Therefore, participants of KPM 29 Multidisciplinary IAIN Ponorogo provide an alternative solution in the form of parenting seminars to parents to reduce excessive dependence on gadgets in children. The method in this service uses the Asset-Based Community-Driven Development (ABCD) approach. The ABCD method emphasizes the identification and utilization of community-owned assets to develop sustainable solutions for guardians. The result of this seminar is that parents now have a more comprehensive understanding of the supervision of gadget use for children and how children can be considered healthy, not only in physical aspects, but also mentally and socially.